Decreased rates of 30-day perioperative complications following ASD-corrective surgery: A modified Clavien analysis of 3300 patients from 2010 to 2014. (March 2019) - Passias, Peter G.; Bortz, Cole A.; Pierce, Katherine E.; Segreto, Frank A.; Horn, Samantha R.; Vasquez-Montes, Dennis; Lafage, Virginie; Brown, Avery E.; Ihejirika, Yael; Alas, Haddy; Varlotta, Christopher; Ge, David H.; et al.
Highlights: Utilized the Clavien system to classify complications post ASD-corrective surgery. 32.1% of patients suffered at least one Clavien complication. CCI and complications decreased, frailty and invasiveness increased temporally. Rates of Grade II and IV decreased, indicative of surgical improvements. Abstract: The Clavien-Dindo grading allows for broad comparison of perioperative surgical complications, and a temporal analysis of complications following ASD-corrective surgery. NSQIP database was utilized from 2010 to 2014 to isolate patients. Complications were stratified by Clavien complication (Cc) grade, and patients grouped by highest Cc grade: I, II, III, IV, V. Secondary analysis grouped by minor (I, II, III) and severe (IV, V). Comorbidity burden was assessed with a NSQIP-modified Charlson Comorbidity Index (CCI) and frailty was measured with a 5-factor modified frailty index (mFI). From 2010 to 2014, 2971 patients (57 yrs, 58% F) underwent surgery for ASD (3.4 ± 4.1 levels; surgical approach: 46% anterior, 44% posterior, 10% combined), the rate of which increased 0.01% to 0.13. 32% suffered >1 complication. Patient breakdown by Cc grade: 0% I, 25% II, 3% III, 4% IV, 1% V. Severe Cc patients were more comorbid than minor Cc (CCI 2.8 vs 1.8), had longer operative times (394 min vs 251), and higher rates of osteotomy (29% vs 13%) and iliac fixation (16% vs 5%). Overall CCI (2.1–1.7) and perioperative complication rates (55–29%) decreased, despite increasing surgical invasiveness (2.8–4.5) and increasing frailty score (0.14 ± 0.15 vs 0.16 ± 0.16). Rates of Clavien grade II (39.80–22.20%) and IV (9.40–3.50%) complications also decreased, indicative of surgical improvements and effective preoperative patient selection. The decrease in CCI and increase in the modified frailty score may show that we are becoming more cognizant of discerning of comorbidities, but likely to not to have taken into account frailty, which may have an impact on future health socioeconomics.